Hukum Acara Mahkamah Konstitusi dalam Teori dan Praktik - Sumadi, Ahmad Fadlil (Mahkamah Konstitusi Republik Indonesia, 2011)
One of the important substance of Amendment of the Constitution of the Republic of Indonesia Year 1945 is the existence of the Constitutional Court as a state institution that functions to handle certain cases in the field of state administration, in order to maintain the constitution to be implemented in a responsible manner in accordance with the will of the people and democratic ideals. Constitutional Court’s constitutional authority to implement the principle of checks and balances which places all state agencies in the equivalent position so that there is a balance in the administration of state The existence of the Constitutional Court is a real step to correct each other’s performance among state institutions. The Constitutional Court in carrying out justice to examine, hear and decide a case still refers to the organizing principle of judicial power which, among others, is carried out simply and quickly.